Preparation of Iron oxide/palladium nanoparticles modified with carbon quantum dots (Pd@CQD@Fe3O4): insight to anti-cancer effect and ROS generation - Parnian Rajabzadeh; Pooneh Zoorazma; Maryam Abbasi; Seyed Ataollah Sadat Shandiz (Scientific Reports)
Abstract Advances in nanoscience and nanotechnology have facilitated the application of nanoparticles in various biomedical fields. This study synthesized iron oxide/palladium nanoparticles modified with carbon quantum dots (Pd@CQD@Fe₃O₄) and evaluated their cytotoxic and anticancer effects on SK-OV-3 (ovarian carcinoma) and MCF-7 (breast adenocarcinoma) human cell lines. Characterization of Pd@CQD@Fe₃O₄ nanoparticles was performed using SEM, EDS, XPS, VSM and zeta potential analysis. The Pd@CQD@Fe₃O₄-treated group exhibited a significantly increased generation of reactive oxygen species (ROS) compared to the control group. To assess the cytotoxic activities of Pd@CQD@Fe₃O₄ nanoparticles, the MTT assay was utilized, revealing a dose- and time-dependent response. Flow cytometry-based apoptosis assays revealed that cytotoxicity was mediated through apoptosis in both MCF-7 and SK-OV-3 cells. Gene expression analysis utilizing real-time PCR revealed significant alterations in Bax, Bcl-2, caspase-8, and caspase-9 levels following Pd@CQD@Fe₃O₄ treatment. Notably, the Pd@CQD@Fe₃O₄ nanoparticle exhibited higher cytotoxicity against SK-OV-3, MCF-7 cancerous cells compared to normal cells. Caspase-8 mRNA expression increased by 1.40-fold in MCF-7 and 1.11-fold in SK-OV-3 cell lines. Caspase-3/7 protein levels rose by 3.00-fold in Pd@CQD@Fe₃O₄-treated SK-OV-3 cells. Pd@CQD@Fe₃O₄ induced total apoptosis in 79.8% of MCF-7 and 77.01% of SK-OV-3 cells, as confirmed by flow cytometry, indicating strong pro-apoptotic activity in both cell lines. These findings suggest that Pd@CQD@Fe₃O₄ nanoparticles possess potent anticancer activity and offer the potential for targeted drug delivery enhancement.